Pendekatan Konseptual Terhadap Manajemen Operasional Sebagai Fondasi Keberlanjutan Organisasi - Achmad Suyudi Amiruddin; Taufik Nugroho; Ramlawati .; Mahfudnurnajamuddin . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Operations management is a strategic organizational function that plays a crucial role in supporting organizational sustainability. The increasingly dynamic business environment requires organizations not only to focus on efficiency and productivity but also to integrate economic, social, and environmental sustainability principles into their operational systems. This study aims to examine operations management as the foundation of organizational sustainability through a conceptual–theoretical approach. The research method employs a systematic literature review of relevant national academic sources addressing operations management and organizational sustainability. Data analysis is conducted through the identification of key concepts, theoretical synthesis, and the development of a conceptual framework. The findings indicate that operational efficiency, process innovation, digitalization, risk management, and the integration of environmental sustainability practices are key elements that strengthen the role of operations management in achieving long-term organizational sustainability. These results emphasize that operations management should not be viewed merely as a technical function, but as a strategic system that supports organizational resilience and continuity. This study is expected to contribute theoretically to the development of sustainable operations management literature and to provide conceptual guidance for practitioners in designing sustainability-oriented operational systems.